First Molecular Characterization of Sheep Pox Viruses in Northern Ghana, 2023 - Theophilus Odoom; Richard Kwamena Abbiw; David Livingstone Mawuko Blavo; Sherry Ama Mawuko Johnson; Patrick Ababio; Spencer Dugbartey; Irene K. Meki; Tirumala B. K. Settypalli; William G. Dundon; Charles E. Lamien (Viruses, 2025)
Sheep pox (SP) is a contagious viral disease affecting sheep, characterized by fever, respiratory distress, hypogalactia, and skin lesions. In response to a series of outbreaks of pox-like lesions with morbidity (75%) and mortality (37%) rates among sheep in the Upper East Region of Ghana, nasal samples were obtained from affected sheep for diagnosis and characterization. The DNA extracted from these samples was tested using quantitative PCR (qPCR). Positive samples were subjected to further analysis for poxvirus marker genes using conventional PCR. Positive amplicons were sequenced, and phylogenetic analysis was conducted. The characterization and comparison of RPO30, GPCR, EEV glycoprotein, and B22R genes with other isolates demonstrated a close genetic relationship with sheep poxviruses (SPVs) identified in other African and Asian countries. This study represents the first comprehensive characterization of SPV in Ghana, and the data generated will be of significant interest to national and regional veterinary authorities.